Denture adhesive antifungal potency towards the growth of Candida Albicans - Dewi, Siti Utami; Sumarsongko, Taufik; Dewi, Warta (Padjadjaran Journal of Dentistry, 2011)
Denture adhesive is a device that applied to the base of a denture before the denture is inserted into the mouth. The device used to improve denture retention and stabilization. It was thought that added antifungal agent to denture adhesive might be an effective way to inhibit the growth of Candida albicans and prevent denture stomatitis.The study was performed as an experimental laboratory study by an observed antifungal test of denture adhesive against Candida albicans growth using Kirby Bauer diffusion agar method with 5 samples and 3-time repetitions. The conclusion of this study was that the antifungal agent in denture adhesive containing poly (methylvinylether/maleic acid), sodium-calcium mixed partial salt and propyl hydroxybenzoate and denture adhesive containing sodium carboxymethylcellulose couldnt inhibit the growth of Candida albicans.